CLOUD DVR OPTIMIZATION - Epstein, Steve; Morgan, David S; Ovadia-Amsalem, Orly (2018)
In one embodiment, a method, system and apparatus are described for cloud digital video recorder optimization. A cloud based storage unit stores recorded content items in response to recording requests by users from among a plurality of users, each recorded content item belonging to at least one content item type category and each user belonging to at least one user type category. A processor receives log files tracking the recording requests, applies a data-driven procedure to the log files on a basis of at least one of: the at least one content item type category and the at least one user type category, and assigns each recorded content item to a group associated with a second plurality of users and a co-related group of content items of a given content item type category and determines times to delete each recorded content item from the cloud based storage unit. Related methods, systems, and apparatus are also described.